Lucifer. Volume 1, The infernal comedy - Watters, Dan (Sandman Universe., 2019)
"The onetime ruler of Hell has gone missing. Lucifer is MIA. He finds himself imprisoned and crippled by mysterious forces who seek to torment him for their own terrible ends. He also happens to have no idea how he got there. This is the one true tale of what befell the Prince of Lies, the Bringer of Light--Lucifer. The blind, destitute old man, who lives in a small boarding house in a quiet little town, where nothing is quite what it seems and no one can leave. He's trapped, you see? Trapped in a bizarre prison with no memory of how he got there or why. As the Devil soon discovers, the answers lay in wait with his estranged son, Caliban... too bad Lucifer can't find him. Meanwhile, in Los Angeles, Detective John Decker is drawn into a shadowy conspiracy whose widely varied members share a single common purpose: to kill Lucifer Morningstar."--